Improving Students’ Vocabulary Mastery Using Flash Cards - Sinaga, Elisabet (The Explora, 2020)
This paper discusses about improving students’ vocabulary mastery using flash cards. The aims of the paper are: (1) to find out whether and to what extent the use of flash cards can improve students' vocabulary and (2) to describe the strengths and the weaknesses of using flash cards to teach vocabulary. The writer conducted a classroom action research from February to June at the second grade of SDN Bulakan 02, Sukoharjo in the academic year 2011/2012. This research was conducted in two cycles and carried out in four steps namely; planning the action, implementation/action, observation, and reflection. The data of the research were collected by using qualitative and quantitative data collection techniques. The result of the research shows that the use of Flash cardscan improve the students’ vocabulary mastery. It can be seen from the mean score of the test which improve from 56.5 in the pre test to 77.1 in the post test one and 83.7 in the post test two. Using flash cards could make the students pay attention to the lesson properly. It also improved students’ participation in learning vocabulary. They were not shy anymore and highly motivated to join the teaching and learning process.